Pola Komunikasi Keluarga Dalam Mempengaruhi Disiplin Belajar Selama Pembelajaran Daring: indonesia - ria edlina (CV. ITTC INDONESIA, 2021)
The importance of family communication patterns in children's education during online learning is currently a benchmark for disciplining children's learning. Parent-child communication in online learning greatly determines children's learning outcomes. The purpose of this study was to describe the pattern of family communication at public elementary schools that had a decreased discipline effect during the pandemic, namely SDN 02 Kampung Pondok. Where the researchers here chose the key informants are the parents of students who work as housewives. This type of research is qualitative research with a case study method, data collection techniques are carried out by means of observation, interviews, and documentation. Data analysis using the Miles and Huberman model, namely through the process of data reduction, data presentation, and conclusions. The results showed that the family communication patterns of students who work as housewives tend to show a combination of authoritarian, democratic, and permissive. However, among the three communication patterns, parents are more dominant in using Permissive communication patterns, namely parenting parents being too lenient, acceptance of people. high parents but low control, giving freedom to children to express their urges or desires. caused by parents who are too busy with work, busyness or other matters that end up forgetting to educate and care for children properly.